THE TRANSFORMATION OF THE BEUT DARÔH AND KENDURI KHATAM TRADITIONS IN THE URBAN COMMUNITY OF BANDA ACEH CITY - Muhajir Al-Fairusy; M. Ikhwan; Darlis Aziz; Muji Mulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This research examined the issue of religious traditions in Aceh from the perspective of understanding and interpreting the Quran. The research focuses on the beut darôh tradition, which culminates with the ceremony of kenduri khatam. In essence, this indigenous Acehnese ritual has been practiced for a long time in Acehnese culture and is exclusively celebrated during the month of Ramadan. The aim of beut darôh is to color the night during Ramadan after the tarawih prayer is done in every mosque and meunasah (Muslim house of worship), frequently in the midst of rural communities. This ritual culminated at the end of Ramadan with the commemoration of the kenduri khatam. This closing ritual encompasses the entire community. Aceh Besar and Banda Aceh were the primary locations to observe this practice evolving and changing. This research begins with the question,